Implementasi Penilaian Hasil Belajar pada Mata Pelajaran Sejarah Berdasarkan Kurikulum 2013 di SMA Pembangunan Laboratorium UNP - Melli Darti; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2019)
The research aims to find out : (1) the implementation of learning oustcomes assessment of the aspect of attitudes, knowledge, and skills in the 2013 curriculum at SMA Pembangunan Laboratorium UNP, (2) the obstacles faced by teachers in carrying out the assessment of learning outcomes of historical subjects at SMA Pembangunan Laboratorium UNP. This research is descriptive qualitative research. Subject in this study were history subject teachers and vice-principals in curriculum. Data collection techniques used were observation, interviews and documentation. Data were analyzed through data reduction, data presentation and drawing conclusions. Data validity test is done by using source triangulation. The results of the study show that : (1) history subject teachers have not optimally conducted an assessment in accordance with the demands of the 2013 curriculum. In this case it is evident from the many assessments that have not been carried out by history teachers at the SMA Pembangunan Laboratorium UNP, (2) constraints faced by the subject teachers historical lessons in crayying out assessment of learning outcomes are : some history subject teachers do not yet understand the assessment in the 2013 curriculum so that they are still familiar with the previous assessment, the assessment in the 2013 curriculum is too complicated, teachers find it difficult to divide their time because there are too many assessment to fill.